Credit access and happiness: Evidence from Indonesia - Muhammad Yusuf Indra Purnama; Siti Aisyah Tri Rahayu; Mulyanto Mulyanto; Johadi Johadi (University of Merdeka Malang, 2022)
The objective of this study is to investigate household credit access and its impact on happiness. We use data from the Indonesia Family Life Survey (IFLS) and employ Ordinary Least Square (OLS) as well as an Ordered Probit approach to test our empirical framework. Our results reveal that per capita expenditure has positively affects the probability of being granted credit, and people in urban communities benefit more from accessing credit than those in rural areas also document that those who successfully obtain credit tend to increase their probability of being happy. We then recommend an improvement in access to credit, particularly for poor people and those who live in rural communities, as an important policy implication. In addition, a better financial capability and financial literacy should be improved continuously to ensure the positive impact of credit on happiness as the ultimate goal in life.